PENGETAHUAN TENTANG PERILAKU HIDUP BERSIH DAN SEHAT (PHBS) PADA MASYARAKAT DESA TANJUNG MULIA - Sipayung, Miko Valentino (JURNAL PENDIDIKAN IPS, 2025)
The purpose of this study was to find a description of the concept of community knowledge in Tanjung Mulia village, Pagar Merbau sub-district about clean and healthy living behavior. This type of research is quantitative with a descriptive approach. The population in this study is a person who is a resident who has lived in Tanjung Mulia Village for at least 5 years. Due to ensuring they have in-depth experience and understanding in accordance with what is being questioned. The data collection method in this research is through several stages, namely; field observation, in-depth interviews and documentation. The results of the research on Knowledge of Clean and Healthy Living Behavior in the Tanjung Mulia Village Community show that the community has a fairly good understanding of the importance of maintaining cleanliness and environmental health. through a cultural ecology approach, it can be seen that the application of Clean and Healthy Living Behavior (PHBS) in this village is a form of cultural adaptation to the physical and social environment, including in facing challenges from the brick making industry activities. The community actively carries out hygiene practices, such as cleaning up garbage, maintaining waterways, and practicing a healthy lifestyle, which reflects awareness of physical, mental, social, and spiritual health.